Alfred Hitchcock's The Rear Window: Cold War, Spatiality, and the Paranoid Subject / Beatrice Kohler. (Reconstruction: Studies in Contemporary Culture, 2014)
This article investigates the notion of 'Cold War culture' by discussing Alfred Hitchcock's 1954 classic Rear Window with a particular focus on spatiality and paranoia. The cinematic screen is seen as a site where socio-cultural conflict is negotiated and political reality is transcoded into fictional narratives. Over and beyond the body of criticism that discusses the movie as a prime example of scopophilia and cinematic self-reflexivity, this paper attempts to combine extradiegetic politics with intradiegetic aesthetics: emerging from a culture of McCarthyite furor, post-war anxieties regarding the millions of soldiers returning from WWII and governmental infringement on privacy, Rear Window investigates the politics of suspicion, surveillance and individual agency by displacing these issues unto multiple imaginary screens that are subject to a paranoid misreading symptomatic of the American 1950s.